2020
DOI: 10.21608/ejchem.2020.39538.2806
|View full text |Cite
|
Sign up to set email alerts
|

Study of Eco-Friendly Corrosion Inhibition for Mild Steel in Acidic Environment

Abstract: The inhibition effect of Chamaemelum Nobile extract on corrosion of mild steel electrode in 1.0 molar hydrochloric acid was studied using gravimetric analysis and electrochemical methods. Results from the experimental studies have shown that, as the inhibitor concentration increases the inhibition efficiency. The adsorption of the inhibitor molecules on mild steel surface obeys Langmuir adsorption isotherm. Scanning electron microscope performed a surface study with and without inhibitors for mild steel. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… 51 Based on the Langmuir isotherm, it can be concluded that the cationic GS (I H and I Me) is adsorbed on the alloys in the form of a monolayer with a lateral interlink between the GS molecules. The negative value obtained for Δ G ads replicates the spontaneity and great adsorption aptitude of GS molecules on the brass surface and reveals the stability of the formed layer on the brass surface, 52 according to the Δ G ads values of −27.76 and −27.45 kJ/mol for I H and I Me, 53 55 respectively. Δ G ads o values of −20 kJ mol –1 or lower are related to electrostatic attraction between charged molecules and the charged metal (physical adsorption); Δ G ads o values of −40 kJ mol –1 or higher involve charge sharing or transfer from organic molecules to the metal surface to form a coordinate type of bond (chemisorption).…”
Section: Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“… 51 Based on the Langmuir isotherm, it can be concluded that the cationic GS (I H and I Me) is adsorbed on the alloys in the form of a monolayer with a lateral interlink between the GS molecules. The negative value obtained for Δ G ads replicates the spontaneity and great adsorption aptitude of GS molecules on the brass surface and reveals the stability of the formed layer on the brass surface, 52 according to the Δ G ads values of −27.76 and −27.45 kJ/mol for I H and I Me, 53 55 respectively. Δ G ads o values of −20 kJ mol –1 or lower are related to electrostatic attraction between charged molecules and the charged metal (physical adsorption); Δ G ads o values of −40 kJ mol –1 or higher involve charge sharing or transfer from organic molecules to the metal surface to form a coordinate type of bond (chemisorption).…”
Section: Results and Discussionmentioning
confidence: 58%
“…Consequently, the adsorption of HCl molecules was importantly diminished, and the corrosion destruction of the metal surface was maximally reduced . As validated by EDX analysis, the adsorbed inhibitor appeared as white spots covering the whole surface of the tested brass specimen …”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Impedance tests provide insights into surface resistance, capacitance, the inhibitory potential of a substance, and the nature of the inhibition process. Any deviations from a perfect circular shape are attributed to interfacial impedance frequency dispersion, associated with surface non-homogeneity and metal roughness [36][37][38][39] .…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…These substances work by binding the metal surface via chemisorption, physisorption, complexation, or precipitation to block oxygen from reaching the cathode, block hydrogen from diffusing from the cathode, or block metal dissolution (anodic inhibitors) 10 . Recent studies focused on finding new corrosion inhibitors that satisfy the necessary requirements from the technical standpoint, with the most emphasis being placed on inhibitors that are non-toxic or environmentally safe 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%